Potential ecosystem services of urban agriculture: a review - Aerts, Raf; Dewaelheyns, Valerie; Achten, Wouter MJ (PeerJ Preprints, 2016)
Urban agriculture (UA) is increasingly proposed as an environmentally friendly answer to global challenges including urbanization, public health, food security and climate change. We provide an overview of present evidence of ecosystem services delivered by UA that could potentially increase the sustainability of the urban ecosystem, including the often claimed reduced greenhouse gas emissions. There is general agreement that UA is important for local food production, especially in the south; that UA has a role in regulating green and blue water flows, organic waste flows and pollination; and that UA has important socio-cultural values, including an improved quality of city life and increased local community capacity. There is some evidence that UA may also improve human health because of dietary changes in certain social classes, but these are potentially confounded by environmental pollution in the city. Quantitative evidence is very limited for all ecosystem services, but the available data nevertheless suggests that the overall food productivity and the total reductions in greenhouse gas emission are low at global or city-wide scale despite the fact that UA has potential strong effects on food security at the local scale. The current eagerness of industrialized cities to integrate UA into their food policies as an approach to become “climate neutral” or to rely on ecosystem services to become more resilient calls for life cycle assessment studies that accurately quantify emission reductions and other urban ecosystem services of urban agriculture.
Keywords: ecosystem services; food systems; agroecology; EcoHealth; urban ecology